A Mechanistic Study of Dissolution of Pt–Fe Binary Alloys in 0.5 M H2SO4 Solution by Channel Flow Triple Electrode. Issue 4 (1st January 2017) - Ooi, Azusa; Tada, Eiji; Nishikata, Atsushi
Abstract : A channel flow triple electrode (CFTE) was applied for the in situ detection of Fe ions (Fe(II) and Fe(III)) and Pt ions (Pt(II) and Pt(IV)) dissolved from Pt–50at%Fe (Pt–50Fe) and Pt–25at%Fe (Pt–25Fe), under potential cycling in 0.5 M H2 SO4 at 298 K. These ions, dissolved from a Pt–Fe alloy working electrode set upstream in a channel, were simultaneously detected on two Au collector electrodes placed downstream by reducing or oxidizing their dissolved ions. When Pt–50Fe was potential-cycled between 0.05 and 1.4 V vs. standard hydrogen electrode, Fe dissolution was significantly enhanced in a double-layer (DL) charging region (0.25–0.85 V), probably owing to the surface diffusion of Pt atoms. In addition, the Fe dissolution was enhanced by Pt dissolution which takes place in a place-exchange potential region (1.2–1.4 V) and in the reduction potential of Pt oxides (0.9–0.5 V) in the cathodic scan. On the contrary, when Pt–25Fe was potential-cycled between 0.05 and 1.4 V, Fe dissolution was strongly suppressed by a Pt–enriched layer, especially in the potential region for the DL. The dissolution also depended on the upper limit of potential cycling ( E U ) and was significantly suppressed, even for Pt–50Fe, when E U was 0.6 V.